OPTIMALISASI MANAJEMEN SUMBER DAYA MANUSIA DALAM PELESTARIAN LINGKUNGAN UNTUK KEBERLANJUTAN EKONOMI - Septiana, Berlian Septiana; Pramesti, Desta Wulandari Pramesti; Azzahra, Nabila Azzahra; Raizky Rienaldy Pramasha (Jurnal Ilmu Ekonomi dan Bisnis, 2024)
In the modern era marked by environmental crises and economic challenges, the optimization of human resource management (HRM) is key to environmental conservation and economic sustainability. This research aims to analyze the role of HRM in promoting environmentally friendly practices within organizations and their impact on economic performance. Using a qualitative approach, the study collects data through interviews with HRM practitioners and environmental observers. The findings indicate that developing competencies, increasing environmental awareness, and implementing policies that support sustainability can enhance organizational performance and contribute to environmental preservation. These findings highlight the importance of integrating HRM strategies with environmental initiatives to achieve sustainable economic goals. Keywords: human resource management, environmental conservation, economic sustainability, eco-friendly practices, sustainability policies